Composites of Donor-π-Acceptor type configured organic compound and porous ZnO nano sheets as corrosion inhibitors of copper in chloride environment - Nikhil; Ji G.; Prakash R. (My University, 2025)
Donor-π-Acceptor (D-π-A) type compounds are very interesting for corrosion study since they have unique structural configuration. Their high chemical reactivity promotes an easy bonding with the metals, which helps in corrosion inhibition. In this work, ethyl-2-cyano-3-(4-(dimethylamino) phenyl) acrylate (ECDPA) (a D-π-A type compound) is used to restrict the copper loss in 1 M HCl. The impedance analysis portrays that ECDPA saves 75% of copper at its maximum concentration in HCl solution. To further increase the inhibition efficiency, ECDPA-ZnO composites are developed. The ZnO is synthesized hydrothermally and calcined at two different temperatures (300 °C and 500 °C). The morphology of synthesized ZnO changes drastically with calcination; however, the main morphological difference in ZnO at 300 °C (Z3) and ZnO at 500 °C (Z5) is increment of porosity. Hence, two composites are made to analyze the change in corrosion behavior of the composites. The composites are designated as: ECDPA-ZnO at 300 °C to EZ3 and ECDPA-ZnO at 500 °C to EZ5. The characterizations of ZnO, ECDPA and ECDPA-ZnO composites have been performed by UV–visible spectroscopy, FTIR spectroscopy, HRTEM, HRSEM, EDAX and XRD techniques. The corrosion inhibition efficiencies of EZ3 and EZ5 are achieved as 78% and 81%. This fact suggests that ZnO increases the adsorption of ECDPA over copper surface, which is confirmed by Langmuir adsorption analysis and electrochemical atomic force microscopy (EC-AFM) measurements. © 2019